160k views
2 votes
Please solve, m +5=-m-2-5m+7?​

User Findusl
by
5.9k points

2 Answers

5 votes

Answer:

m = 0

Explanation:

m + 5 = - m - 2 -5m + 7

m + 5 = -m - 5m - 2 + 7

m + 5 = -6m + 5 (combine like terms)

m = 0

User Vetsin
by
6.0k points
6 votes

Answer:


\Huge \boxed{m=0}

Explanation:


m +5=-m-2-5m+7

Adding m and 5m to both sides of the equation.


m +5+m+5m= -m-2-5m+7+m+5m

Subtracting 5 from both sides of the equation.


m +5+m+5m-5=-2+7-5

Combining like terms and simplifying.


7m=0

Dividing both sides of the equation by 7.


m=0

User DigiKev
by
6.4k points